1998
DOI: 10.2337/diacare.21.4.563
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Impaired Glucose Tolerance in Three Alaskan Eskimo Populations: The Alaska-Siberia Project

Abstract: These prevalences of diabetes are the highest yet reported among Eskimo populations. Obesity and family history of diabetes are associated with increased odds of developing diabetes. These data underscore the need to further examine risk factors and to design effective interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 12 publications
5
80
0
Order By: Relevance
“…19 The percentage of eligible residents that participated in the screening clinic was 69% among the Central Yupik, 55% among the Inupiat, and 44% among the Siberian Yupik people. Participation was higher for the older age groups with 66% of those !45 y and 41% of those`45 y participating.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The percentage of eligible residents that participated in the screening clinic was 69% among the Central Yupik, 55% among the Inupiat, and 44% among the Siberian Yupik people. Participation was higher for the older age groups with 66% of those !45 y and 41% of those`45 y participating.…”
Section: Resultsmentioning
confidence: 99%
“…26 ± 30 Welty detailed the health implications of obesity for American Indians and Alaska Natives, which include diabetes, cardiovascular disease and hypertension among other maladies. 31 For Alaska Natives speci®cally, both Murphy et al 2 and this project 19 have demonstrated an association of BMI with glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…25 The western lifestyle implies a larger intake of food with a high glycaemic load 26 and less developed societies adopting the western dietary pattern experience increasing incidences of hyperglycaemia, insulin resistance, hyperinsulinaemia, and type 2 diabetes. 27,28 A high glycaemic load imposes acute and chronic hyperinsulinaemia, 25 and a large intake of sucrose lowers the insulin sensitivity 29 and blocks the binding of insulin to the receptor. 30 Cordain et al 25 argue that high glycaemic load and the resulting hyperinsulinaemia affect different growth factors resulting in scleral growth.…”
Section: Diet and Diabetesmentioning
confidence: 99%
“…Members of these more natural populations are protected from the illnesses of civilization only as long as they live their native lifestyle. As soon as they move to cities and accommodate to more modern conditions, the incidence of chronic diseases (among them acne) increases [19,21,28].…”
Section: The Early Years: Twin Family Community-based and Cross-sementioning
confidence: 99%